1974
DOI: 10.1136/bmj.4.5939.253
|View full text |Cite
|
Sign up to set email alerts
|

Ischaemic Heart Disease in Young Women

Abstract: SummaryThe mortality rate from ischaemic heart disease (I.H.D.) has increased in young women by about 50% in 12 years, and it is now possible to report the findings in 150 women who developed symptoms Hypercholesterolaemia, hypertension, or excessive cigarette smoking each occurred in a large minority, and more than one of these major risk factors was present in most patients. Hypercholesterolaemia was the commonest factor. In women in whom lipoprotein typing was undertaken the type II pattern was more frequ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
26
1
1

Year Published

1979
1979
2017
2017

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 109 publications
(28 citation statements)
references
References 22 publications
0
26
1
1
Order By: Relevance
“…First, 2 studies have linked a lifelong history of menstrual irregularity with a significantly increased risk for acute myocardial infarction. 175,176 A third study has shown that irregularly menstruating women, in comparison with normally cycling control women, have elevated plasma fibrinogen concentrations (a risk factor for CAD) and a thickened arterial intima. 177 The possibility that these observations might reflect the reduced concentrations of endogenous estrogen characteristic of ovary-impaired women is supported by the finding that premenopausal women with angiographically confirmed CAD have significantly lower plasma estradiol concentrations than do control subjects and that such levels resemble those observed in subordinate female monkeys.…”
Section: Sex Differencesmentioning
confidence: 99%
“…First, 2 studies have linked a lifelong history of menstrual irregularity with a significantly increased risk for acute myocardial infarction. 175,176 A third study has shown that irregularly menstruating women, in comparison with normally cycling control women, have elevated plasma fibrinogen concentrations (a risk factor for CAD) and a thickened arterial intima. 177 The possibility that these observations might reflect the reduced concentrations of endogenous estrogen characteristic of ovary-impaired women is supported by the finding that premenopausal women with angiographically confirmed CAD have significantly lower plasma estradiol concentrations than do control subjects and that such levels resemble those observed in subordinate female monkeys.…”
Section: Sex Differencesmentioning
confidence: 99%
“…Evidence of myocardial ischaemia in the electrocardiogram of the resting patient was as defined by Oliver (1974), namely Code 4,1 or 5,1: ST depression of 1.0 mm or more, or T wave inversion of 5.0 mm or more, respectively.…”
Section: Methodsmentioning
confidence: 99%
“…In only two patients was there electrocardiographic evidence of ischaemia as defined in the methods section; however, both these patients had identical patterns before the drug was given. Two other patients had slight deepening of T wave inversion on the day following labetalol administration (code 5, 3 to 5, 2), but in neither instance did this exceed 2 mm, and did not satisfy Oliver's (1974) criteria for ischaemia. One patient showed disappearance of a 4, 2 abnormality (ST depression of 0.6 mm) after labetalol treatment.…”
Section: Changes In Heart Ratementioning
confidence: 97%
“…Although reports of associations of coronary disease risk with parity, age at menarche, or incidence of miscarriage are not all consistent (7,8) (10,14). (17)(18)(19)(20).…”
Section: Abstract: a Woman's Reproductive History May Affect Her Riskmentioning
confidence: 99%